Spectroscopic study on peculiarities of fumed silica hydridesilylation with triethoxysilane under fluidized bed conditions - P. O. Kuzema; A. V. Korobeinyk; V. A. Tertykh (Хімія, фізика та технологія поверхні)
Fumed silica has found widespread application in industry due to variety of fascinating properties. Owing to its specific manufacturing process, it consists of finely dispersed particles and is featured with large specific surface area covered by profoundly reactive silanol groups which are available for chemical grafting. Spherical shape of fumed silica particles and lacking porosity provides a space-filling structure. These characteristics implement the fume silica’s utilization as high-surface-area carriers for various catalysts, i.e. metallic nanometer-sized particles, organic moieties, etc. Currently a great attention is called to on-surface grafting to improve the silica-based carrier. Most of research is carried out in area of liquid phase chemistry involving an abundance of expensive and often toxic solvents while the space-filling properties of silica are favoring reactions in fluidized bed conditions.